SAT0521 A prospective observational study on the safety and efficacy of infliximab-biosimilar in patients with takayasu's arteritis (TAKASIM): preliminary data. (12th June 2018) - Campochiaro, C.; Tomelleri, A.; Sartorelli, S.; Sembenini, C.; Cavalli, G.; Baldissera, E.; Dagna, L.
Abstract : Background: Takayasu arteritis(TA) is a large-vessel vasculitis 1 . Treatment is mainly based on steroids, but in approximately 50% of patients a disease-modifying antirheumatic drug(DMARD) is required 2 . Anti-TNFα agents are recommended for steroid tapering despite DMARDs 3 . Infliximab-originator(IFX-O) is a chimeric monoclonal antibody against TNFα effective in TA patients. Infliximab-biosimilar(IFX-B) is an immunoglobulin-G1 chimeric human-murine monoclonal antibody biosimilar to IFX-O. Objectives: To assess safety and efficacy of IFN-B in TA patients requiring anti-TNFα therapy. Methods: 30 TA patients, diagnosed according to ACR criteria at our tertiary centre, will be recruited from our cohort. Both biological therapy-naïve and IFX-O treated patients will be eligible. Disease activity will be assessed 6-monthly by means of magnetic resonance angiography(MRA) and 18 F-fluorodeoxyglucose(FDG) PET/CT. ITAS2010 and ITAS-ESR/CRP will be obtained 6-monthly. Baseline was defined as the time of IFX-B start. Non parametric statistic tests were used. Results: At January 2018, 19 patients(18 female, 1 male) were included. 12 patients have been on IFX-B for at least 6 months. Median age at baseline was 45 years(range 25–70). At recruitment median disease duration was 52 months(range 24–180), all patients were on IFX-O. Median time on IFX-O at baseline was 35 months(range14–150). 3 patients had been previously treated with other biologics: tocilizumab(, 2 adalimumab(. 1 18/19 patients(94.7%) were on concomitant steroid therapy(mean dose 5±1.8 mg). It was significantly reduced to a mean dose of 4±1.7 mg(p=0.043) at month 6. 15/19 patients(78.9%) were also on DMARDs, kept unchanged throughout treatment. 1 patient on IFX-B was switched to a different therapy because of poor disease control with both IFX-O and IFX-B. Mean IFX-B dose at baseline was 6.92±1.76 mg/kg. Mean IFX-B dose at month 6 was 7.42±2.19 mg/kg. IFX-B dose was increased in 5 patients. Mean time interval between IFX-B infusions was kept unchanged(5.79±0.63 weeks). Mean CRP and ESR were 3.28±2.64 mg/L and 19.68±9.94 mm/1 hour at baseline and 3.4±3.12 mg/L and 20.53±14.06 mm/1 hour at month 6, the difference not being statistically significant. Mean ITAS2010 and ITAS-ESR/CRP were 7.6, 8.2 and 8 at baseline and 6.1, 6.8 and 6.3 at month 6, the difference not being statistically significant. At month 6 PET/CT showed no disease progression in all patients and MRA disclosed disease stability in 8/12 (66.7%), progression in 3/12 (25%) and improvement in 1 (8.3%) patient. No patient experienced side effects during infusion. 11/19 patients(57.9%) experienced low-grade side effects related to TNFα blockade. 6 patients experienced upper airway infection, 3 herpes simplex reactivation, 1 viral gastroenteritis, 1 vaginal candidiasis. No modification of IFX-B therapy was required. Conclusions: Our preliminary data suggest that IFX-B is as effective and safe as IFX-O in TA patients. References: [1] Numano F, et al. Takayasu's arteritis. Lancet2000. [2] Hoffman GS, et al. Treatment of glucocorticoid-resistant or relapsing Takayasu arteritis with methotrexate. Arthritis Rheum1994. [3] Clifford A, et al. Recent advances in the medical management of Takayasu arteritis: an update on use of biologic therapies. Current Opinion in Rheumatology2014. Disclosure of Interest: C. Campochiaro: None declared, A. Tomelleri: None declared, S. Sartorelli: None declared, C. Sembenini: None declared, G. Cavalli: None declared, E. Baldissera: None declared, L. Dagna Grant/research support from: The Unit has received unrestricted educational grants from Abbvie, BMS, Celgene, Mundipharma, Novartis, MSD, Pfizer, Roche, and SOBI.